Closed Season and the Distribution of Small-Scale Fisheries Fishing Effort in Davao Gulf, Philippines - Edison D. Macusi; Andre Chagas da Costa-Neves; Christian Dave Tipudan; Ricardo P. Babaran (World, 2023)
The Davao Gulf supports various livelihoods and activities for small-scale and commercial fisheries. However, facing a declining catch, a closed season was implemented to arrest the decline. This study aimed to describe the Davao Gulf fisheries, determine the movement patterns of fishing boats during closed and open seasons, and quantify and compare their catch and their fishing distances. Boat tracking was combined with catch logbook monitoring of fishers and supplemented with interview surveys (N = 35) and mapping surveys (N = 167), including the use of secondary catch data. Results from the interviews showed that the average age of the fishers was 45 years old, with 27 years of fishing experience using motorized boats with 8 HP engines. Their average catch was 7 kg per trip dominated by big-eyed scad (Selar crumenophthalmus), frigate tuna (Auxis thazard), roundscad (Decapterus spp.), skipjack tuna (Katsuwonus pelamis), and yellowfin tuna (Thunnus albacares). There were highly significant differences between the volume of catch of small-scale fishers and commercial fishers after the closure in 2014 (278 t vs. 80 t; p < 0.001) and between the species caught (p < 0.001). Fishing activities were associated with a speed class of 0–1 km/h, while the average moving speed was 5.28 km/h. Fishing ground overlap was common among fishers from the same port of origin but not fishers of different ports. Some fishers move farther away from their port during the closure period. Our study provided a better understanding of fishing effort distribution in the Davao Gulf.